PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PEMBIBITAN KELAPA SAWIT - Sari K. D.; Panupesi H; Syahrudin Syahrudin (AgriPeat, 2015)
The purpose of the research to study the effect of growing media composition on plant growth palm oil in pre nursery. The design used was completely randomized design (CRD) with one factor, namely the composition of the planting medium with a mixture of fertilizer Petroganik (M) with 6 treatments, namely : M1 (3 kg of alluvial + 1 kg of manure + 1 kg of sandy soil), M2 (3 kg of peat soil + 1 kg of manure + 1 kg of sandy soil), M3 (3 kg of alluvial + 1 kg of manure + 1 kg of sandy soil + 0.25 kg of organic fertilizer), M4 (3 kg of peat soil + 1 kg of manure + 1 kg of sandy soil + 0.25 kg of organic fertilizer), M5 (3 kg of alluvial + 1 kg of manure + 1 kg of sandy soil + 0.50 kg of organic fertilizer) and M6 (3 kg of peat soil + 1 kg of manure + 1 kg of sandy soil + 0.50 kg of organic fertilizer). The variables measured were plant height, number of leaf midrib, leaf area, fresh weight and dry weight of the total oil palm seedlings. The results showed that the composition of the planting medium with a mixture of fertilizer Petroganik significant effect on all variables palm seedling growth (plant height, number of leaf midrib, leaf area, fresh weight and dry weight of the total) in pre nursery. The composition of the planting media of 3 kg alluvial + 1 kg of manure + 1 kg of sandy soil + 0.25 kg organic fertilizer had a significant effect onthe growth of oil palm seedlings in the pre ursery. Key Word : Palm oil, growing media and organic fertilizer.